PENGARUH EKSPOR TEH INDONESIA, 2000-201 - Wanda Wuri; Ahmad Zafrullah TN.; Idfi Setyaningrum (CALYPTRA, 2018)
Tea has a significant contribution to Indonesia's economic subsector by contributing through export activities every year. The main object of this research is to identifty and analyze factors inffluencing most toward export volume Indonesian tea. Data which is used is the secondary data and used quantitative approach (time seires) from 2000 to 2015 period were further analyzed using the Ordinary Least Square (OLS). The independent variables used in this study are export price of Indonesian tea, domestic price of Indonesian tea and exchange rate, while the dependent variable used in this study is the export volume of Indonesian tea. The result shows that all the long run the variables that influence significantly to export volume are export prices, domestic prices and exchange rate.